Predictors of and barriers to service use for children at risk of ADHD: longitudinal study - Sayal, Kapil; Mills, Jonathan; White, Kate; Merrell, Christine; Tymms, Peter (Springer, 2015)
Objective Many children with, or at risk of, ADHD do not receive healthcare services for their difficulties. This longitudinal study investigates barriers to and predictors of specialist health service use.